Seed priming and media for enhanced seed germination traits in pansy (Viola tricolor) - THAKUR, TANYA; DHATT, K.K. (Journal of Ornamental Horticulture, 2024)
The present study was conducted to evaluate the effect of seed treatments and growing media on seed germination parameters of pansy at Punjab Agricultural University, Ludhiana during 2020-21. The seeds were given pre sowing treatment for 24 hours with seven different chemicals i.e. control/water, Thiourea @ 50 ppm, KNO3 @ 0.1%, KNO3 @ 0.2%, GA3 @ 25 ppm, GA3 @ 50 ppm, GA3 @ 75 ppm, and grown in six different media compositions i.e. soil: FYM (1:1), soil: sand: vermicompost (1:1:1), soil: sand: FYM (1:1:1), soil: sand: leaf manure (1:1:1), soil: cocopeat: vermicompost (1:1:1) and soil: leaf manure (1:1) in the month of October. The seeds treated with GA3 @ 25 ppm resulted in lowest germination period (23.89 days), maximum imbibition period (16.50 days) germination percentage (80%), germination index (0.63), rate of emergence (16.55) and vigor index (7.87). Among different media treatments, seed sown in soil: cocopeat: vermicompost (1:1:1) recorded the lowest germination period (24.14 days), maximum imbibition period (12.52 days), germination percentage (79.84%), germination index (0.60), rate of emergence (16.72), survival percentage (82.38%) and vigor index (8.01). Considering the interaction between media and seed treatments, the combination of GA3 @ 25 ppm with soil: cocopeat: vermicompost (1:1:1) recorded lowest germination period (23.33 days), maximum imbibition period (10.00 days), germination percentage (87.77%) and vigor index (9.23). Therefore, it could be concluded that the pansy seeds treated with GA3 @ 25 ppm and grown in soil: cocopeat: vermicompost (1:1:1) composition recorded improved seed germination traits.